1992
DOI: 10.1111/j.1600-0714.1992.tb00979.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical detection of herpes viruses in oral smears of HIV‐infected patients

Abstract: Langford A, Kunze R, Sehmelzer S, Wolf H, Pohle H-D, Reichart P: Immunocytochemical detection of herpes viruses in oral smears of HIV-infected patients. J Oral Pathol Med 1992; 21: 49-57.Cytologie smears (CS) were taken from the lateral border of the tongue of HIVseropositive patients (HlV-f) {n = 39) and of seronegative controls (HIV-) (n = 19) and examined by immunocytochemistry (APAAP) and in situ hybridization (ISH) (biotinylated DNA probes) for the presence of viral antigens/DNA of EBV and CMV. While none… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Our results show that, in clinically normal oral mucosa of immunodeficient subjects, HPV, EBV and, less frequently, CMV are present and easily detectable by PCR from epithelial brushings. EBV‐DNA, has been shown to be the most frequently present genome in our study groups, and its presence should be monitored in HIV + patients, especially among men, in order to prevent or to diagnose early the possible occurrence of OHL (Langford et al , 1992).…”
Section: Discussionmentioning
confidence: 94%
“…Our results show that, in clinically normal oral mucosa of immunodeficient subjects, HPV, EBV and, less frequently, CMV are present and easily detectable by PCR from epithelial brushings. EBV‐DNA, has been shown to be the most frequently present genome in our study groups, and its presence should be monitored in HIV + patients, especially among men, in order to prevent or to diagnose early the possible occurrence of OHL (Langford et al , 1992).…”
Section: Discussionmentioning
confidence: 94%
“…31 The detection of EBV in the mucosa has been performed using various techniques, such as PCR, in situ hybridization, immunohistochemistry, and electron microscopy. 12,15,18,[32][33][34] The material to be examined may be collected by biopsy or cytological examination of the oral mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…12,14 With the objective of performing less invasive diagnostic procedures, studies have shown exfoliative cytology to be an alternative approach to biopsy analysis for diagnosis. [15][16][17][18][19] Pap-stained cytological smears of hairy leukoplakia show nuclear changes such as Cowdry type A inclusions surrounded by a clear zone, a homogeneous nuclear membrane, peripheral margination of chromatin, and ground-glass nuclei (Figure 1e). However, the diagnostic accuracy of Pap smears for EBV infections is of low sensitivity and specificity because the cytopathological changes induced by EBV overlap with those of herpetic nuclear inclusions and are not pathognomonic.…”
Section: Herpes Virusesmentioning
confidence: 99%
“…The current gold standard for definitive diagnosis of hairy leukoplakia is EBV ISH 12,14 . With the objective of performing less invasive diagnostic procedures, studies have shown exfoliative cytology to be an alternative approach to biopsy analysis for diagnosis 15–19 . Pap‐stained cytological smears of hairy leukoplakia show nuclear changes such as Cowdry type A inclusions surrounded by a clear zone, a homogeneous nuclear membrane, peripheral margination of chromatin, and ground‐glass nuclei (Figure 1e).…”
mentioning
confidence: 99%
See 1 more Smart Citation